Intelligent medication manager: developing and implementing a mobile application based on WeChat - Liu, Jian; Wu, Yalan; Wang, Yuhua; Fang, Pingfei; Zhang, Bikui; Zhang, Min (Frontiers in Pharmacology, 2023)
Background: Time and space constraints have often hindered the provision of optimal pharmaceutical care, limiting medication therapy management. Social media tools have gained significant popularity in the field of pharmaceutical care. This study aimed to develop a WeChat-based intelligent medication manager platform that facilitates online pharmaceutical care and encourages self-management.We developed a WeChat-based Internet pharmacy service platform called Xiang Medicine Guidance (XMG). Through the analysis of surveys and user access data, we evaluated the demand and utilization of the XMG platform and assessed patients' satisfaction with its services. Patients' adherence before and after the XMG platform intervention was also investigated.The XMG platform was launched in November 2022, offering medication guidance, reminders, and consultation services through the WeChat mini-program. By the end of April 2023, the platform had attracted 141.2 thousand users, accumulating 571.0 thousand visits. Moreover, 1,183 clients sought online medication consultations during this period. Six months after the launch of XMG, an impressive 91.02% of users expressed their satisfaction with the platform. The medication reminders and consultations provided by XMG significantly contributed to medication adherence, with 56.02% of users categorized as having good adherence, better than the previous 47.26%.Through its services and features, XMG empowers patients to better manage their medications, seek professional advice, and adhere to their prescribed treatment plans. XMG has the potential to positively impact public health on a broader scale.